Advanced maternal age: maternal and perinatal outcomes - Sharma, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Advanced maternal age is significantly associated with adverse obstetrical outcomes like pregnancy-induced hypertension and preterm Delivery. Caesarean delivery is also increased in those mothers. Advanced maternal age pregnancy was also found to be a major risk factor for low birth-weight and perinatal death. Methods: A hospital based observational study was conducted with 100 patients on attending antenatal-OPD patients at K. J. Somaiya Medical College and Research centre to evaluate the risks involved with advanced maternal age, the obstetric performance with neonatal outcomes of elderly gravidas aged 33 years or older. Results: The most common maternal complication was gestational diabetes mellitus (16%), pregnancy induced hypertension (13%), pre-eclampsia (11%), malpresentation (8%), oligohydramnios (6%), placenta previa (2%) and post-partum haemorrhage (2%). Caesarean Section in 39% cases and vaginal delivery in 61% cases. (78%) were term deliveries, (22%) were preterm deliveries. (9%) neonates were very low birth weight [<1.5 kg, (34%) neonates were low birth weight (1.5-2.5 kg)] (36%) and (21%) neonates were in the range of 2.6-2.9 kg and ≥3 kg respectively. Conclusions: Advanced maternal age is significantly associated with adverse obstetrical outcomes like pregnancy-induced hypertension and preterm delivery. Caesarean delivery was increased in those mothers. Advanced maternal age pregnancy was found to be a major risk factor for low birth-weight, perinatal death. Therefore, it is better for health care providers to counsel couples, who seek to have a child in their later ages, about the risks of advanced maternal age pregnancy.